Party system fragmentation and PAC performance: the Case of India - Pelizzo, Riccardo; Kindra, Gurprit (My University, 2012)
While the political consequences of party system fragmentation have extensively been discussed in the literature, little to no attention has been paid to whether the fragmentation of the party system affects the performance of public accounts committees. The purpose of this paper is to fill this gap by investigating the relationship between the fragmentation of the Indian party system on the one hand and the performance of the Indian public account committee. The evidence presented in the paper sustains the claim that such relationship is curvilinear which means that rising levels of fragmentation are beneficial to PAC performance up to a certain point, while they prevent its effective performance when they exceed a critical value.
Keywords: Indian party; party systems; parties; Party system fragmentation; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science